A Review of The Role of Architecture in Encouraging Socio-Community Integration in Nature Schools - Agrian Rizki Kuswanto; Puteri Fitriaty; Irdinal Arief (Universitas Muhammadiyah Surakarta, 2026)
Social-community integration is an important aspect in the development of Nature-Based Schools as an educational model that emphasizes interaction with nature and social collaboration. This study aims to analyze the role of architecture in promoting social-community integration in Sekolah Alam through a literature review. The method used is a systematic literature review of various sources discussing the concepts of educational architecture, social spaces, and Sekolah Alam. The findings indicate that architectural designs that accommodate open spaces, flexible circulation, and the use of natural materials can enhance social interaction and strengthen the sense of togetherness among school community members. In addition, the application of inclusive and multifunctional design principles also contributes to the creation of a supportive and harmonious learning environment. In conclusion, architecture plays a strategic role in building social-community integration in Alam Schools , and thus should be a key consideration in the planning and development of sustainable nature-based schools. This study provides a scientific basis for the design of educational spaces that optimize social interaction and environmental sustainability.